Mechanical properties and structural performance of sustainable lightweight aggregate concrete using blended oil palm bio products / Muhammad Aslam - Muhammad , Aslam (2017)
A number of materials have been proposed for producing structural grade of lightweight concretes. However, the main concerns of civil engineers and researchers to develop a proper structural lightweight concrete are cost effective, being environmental friendly and durable, as well as behaves satisfactorily under structural applications. Although several types of artificial lightweight aggregates are available to produce structural lightweight concrete, however, these types of aggregates require huge amount of energy in their preparation. Therefore, use of industrial waste as an alternative lightweight aggregate to build environmentally sustainable structures has several practical and economic advantages. Oil palm shell (OPS) is a solid waste material from the palm oil industry that has been successfully used to produce high strength lightweight concrete. However, this type of concrete is very sensitive to a poor curing environment. In addition, OPS concrete with normal and high strengths have relatively high drying shrinkage at early and later ages. Therefore, to produce a cleaner and greener concrete, this study tried to resolve disadvantages of OPS lightweight concrete using another type of lightweight aggregate waste origin from palm oil industry namely oil-palm-boiler clinker (OPBC). Therefore, a new high strength lightweight concrete containing blended coarse lightweight aggregates was developed and its mechanical and time-dependent properties as well as structural performance in term of shear behaviour of simply supported reinforced concrete beams were investigated. It was found from this study that use of blended OPS and OPBC can produce a workable high strength lightweight concrete with a 28-day compressive strength in the range of 40 to 53 MPa and dry density less than 2000 kg/m3. The individual use of OPBC as coarse aggregate can produce high strength semi-lightweight concrete with 28-day compressive strength of 60 MPa and dry density of 2050 kg/m3. Test results showed that when OPS concrete is very sensitive to poor curing and minimum period of 7 days moist curing is recommended for this concrete, the sensitivity of compressive strength of concrete to the lack of curing is significantly reduced when OPS was partially replaced with OPBC. The substitution of OPS with OPBC significantly improved the splitting tensile and flexural strengths as well as the modulus of elasticity of the concretes. Concretes containing blended coarse lightweight aggregates of OPS and OPBC showed initial and final water absorption of less than 3% and 10%, respectively, and can be considered as good quality concrete. Drying shrinkage strain value of OPS and OPS-OPBC blended coarse concretes is found to be similar at early ages. However, the long-term shrinkage of blended coarse concretes was significantly lower than OPS concrete. Under 7-day initial moist curing condition, OPS concrete showed significantly higher drying shrinkage of about 47%, 41% and 39% compared to the shrinkages of normal weight, artificial lightweight and OPBC concretes at one year age. In structural performance, OPS reinforced concrete beams without shear links showed lower ultimate load carrying capacity compared to the blended coarse lightweight concrete beams. However, higher substitution of OPBC in OPS concrete with high grade concrete significantly improved the structural performance and failure nature of the beams.